THE EFFECT OF AUDIT FEE, AUDIT TENURE, AND FIRM SIZE ON AUDIT QUALITY - Regina, Michelle; Santioso, Linda (Graduate Program of Universitas Tarumanagara, 2023)
The aim of this study is to obtain empirical evidence regarding the effect of audit fee, audit tenure and firm size on audit quality in finance companies listed on the Indonesia Stock Exchange in 2018 – 2020. This study uses a purposive sampling method with 38 finance companies listed on the Indonesian Stock Exchange. The data in this study were inputted and calculated using the Microsoft Excel program and processed using the EViews 9.0 program. The result of this study indicate that audit fee has a significant negative effect on audit quality while audit tenure has no significant value on audit quality and firm size has a significant positive effect on audit quality.